From traditional biochemical signals to molecular markers for detection of sepsis after burn injuries. Issue 1 (February 2019) - Muñoz, Balam; Suárez-Sánchez, Rocío; Hernández-Hernández, Oscar; Franco-Cendejas, Rafael; Cortés, Hernán; Magaña, Jonathan J.
Highlights: Biomarkers should be suitable for early diagnosis of sepsis in burned patients. Biomarkers may include proteins or RNA, and genetic markers such as polymorphisms may help to establish susceptibility. Novel methods of extraction and detection of biomarkers based on new technologies will offer Point-Of-Care (POC) diagnostics. Abstract: Sepsis is a life-threatening organ-dysfunction condition caused by a dysregulated response to an infectious condition that can cause complications in patients with major trauma. Burns are one of the most destructive forms of trauma; despite the improvements in medical care, infections remain an important cause of burn injury-related mortality and morbidity, and complicated sepsis predisposes patients to diverse complications such as organ failure, lengthening of hospital stays, and increased costs. Accurate diagnosis and early treatment of sepsis may have a beneficial impact on clinical outcome of burn-injured patients. In this review, we offer a comprehensive description of the current and traditional markers used as indicative of sepsis in burned patients. However, although these are markers of the inflammatory post-burn response, they usually fail to predict sepsis in severely burned patients due to that they do not reflect the severity of the infection. Identification and measurement of biomarkers in early stages of infection is important in order to provide timely response and effective treatment of burned patients. Therefore, we compiled important experimental evidence, demonstrating novel biomarkers, including molecular markers such as genomic DNA variations, alterations of transcriptome profiling (mRNA, miRNAs, lncRNAs and circRNAs), epigenetic markers, and advances in proteomics and metabolomics. Finally, this review summarizes next-generation technologies for the identification of markers for detection of sepsis after burn injuries.